Failing to Make Ends Meet: The Broad Clinical Spectrum of DNA Ligase IV Deficiency. Case Series and Review of the Literature - Staines Boone, Aidé Tamara; Chinn, Ivan K.; Alaez-Versón, Carmen; Yamazaki-Nakashimada, Marco A.; Carrillo-Sánchez, Karol; García-Cruz, María de la Luz Hortensia; Poli, M. Cecilia; González Serrano, M. Edith; Medina Torres, Edgar A.; Muzquiz Zermeño, David; Forbes, Lisa R.; Espinosa-Rosales, Francisco J.; et al. (Frontiers in Pediatrics, 2019)
DNA repair defects are inborn errors of immunity that result in increased apoptosis and oncogenesis. DNA Ligase 4-deficient patients suffer from a wide range of clinical manifestations since early in life, including: microcephaly, dysmorphic facial features, growth failure, developmental delay, mental retardation; hip dysplasia, and other skeletal malformations; as well as a severe combined immunodeficiency, radiosensitivity and progressive bone marrow failure; or, they may present later in life with hematological neoplasias that respond catastrophically to chemo- and radiotherapy; or, they could be asymptomatic. We describe the clinical, laboratory and genetic features of five Mexican patients with LIG4 deficiency, together with a review of 36 other patients available in PubMed Medline. Four out of five of our patients are dead from lymphoma or bone marrow failure, with severe infection and massive bleeding; the fifth patient is asymptomatic despite a persistent CD4+ lymphopenia. Most patients reported in the literature are microcephalic females with growth failure, sinopulmonary infections, hypogammaglobulinemia, very low B-cells, and radiosensitivity; while bone marrow failure and malignancy may develop at a later age. Dysmorphic facial features, congenital hip dysplasia, chronic liver disease, gradual pancytopenia, lymphoma or leukemia, thrombocytopenia and gastrointestinal bleeding have been reported as well. Most mutations are compound heterozygous, and all of them are hypomorphic, with two common truncating mutations accounting for the majority of patients. Stem-cell transplantation after reduced intensity conditioning regimes may be curative.